Relações entre engajamento de stakeholders e cocriação de: da revisão sistemática com digitalização à medição do efeito na transformação digital - Silva, Luís Fábio Cavalcanti da (2022)
The objective of the present work is to investigate in depth the relationship between digitization, stakeholder engagement and value co-creation. To achieve this objective, I carried out two studies: i) a Systematic Review of Literature (RSL) from 82 published articles, making a thematic and theoretical analysis to identify the theoretical relationships between the investigated constructs; and ii) an empirical study, with the analysis of structural equations and statistical tools, to investigate the effect of digital transformation (one of the dimensions of digitization) on the relationship between stakeholder engagement and value co-creation. As it is a seminal and theoretical work, the first study was carried out comprehensively, in a broad research context. The second study was carried out with the delimitation of the B2B (business to business) context. The main results of study 1 present the dimensions of digitization (digital technology, digital innovation, digital platforms, digital servitization and digital transformation) and the occurrence of relationships between the constructs, according to each dimension. The main results of study 2 indicate the existence of an antecedent relationship between stakeholder engagement and value co-creation, as well as a partial mediation effect of digital transformation in the relationship. tion between stakeholder engagement and value cocreation. This work contributes to theory and research as it gathers, analyzes and relates works already carried out, in a systematic and unprecedented way, facilitating the beginning of new research or more in-depth works on the subject. In addition, still in the theoretical field, the work presents the coupling between the stakeholder engagement theory and the value cocreation theory and an analysis of the effects of digital transformation, something also m unpublished. The empirical contribution consists of providing organizations and the managerial field with a rich study material, with the use of practices and strategies that can lead to a better understanding of and co-creation of value, in a digital environment, increasingly collaborative and also more competitive.